Determinants of quality of life in degenerative cervical myelopathy: a systematic review. (2nd January 2023) - Hirayama, Yuri; Mowforth, Oliver D.; Davies, Benjamin M.; Kotter, Mark R. N.
Abstract: Background: Degenerative cervical myelopathy (DCM) is the most common cause of chronic, progressive spinal cord impairment worldwide. Patients experience substantial pain, functional neurological decline and disability. Health-related quality of life (HRQoL) appears to be particularly poor, even when compared to other chronic diseases. However, the determinants of HRQoL are poorly understood. The objective was to perform a systematic review of the determinants of quality of life of people with DCM. Methods: A systematic search was conducted in MEDLINE and Embase following PRISMA 2020 guidelines (PROSPERO CRD42018115675). Full-text papers in English, exclusively studying DCM, published before 26 March 2020 were eligible for inclusion and were assessed using the Newcastle-Ottawa Scale and the Cochrane Risk of Bias 2 (RoB 2) tool. Study sample characteristics, patient demographics, cohort type, HRQoL instrument utilised, HRQoL score, and relationships of HRQoL with other variables were qualitatively synthesised. Results: A total of 1176 papers were identified; 77 papers and 13, 572 patients were included in the final analysis. A total of 96% of papers studied surgical cohorts and 86% utilised the 36-Item Short Form Survey (SF-36) as a measure of HRQoL. HRQoL determinants were grouped into nine themes. The most common determinant to be assessed was surgical technique (38/77, 49%) and patient satisfaction and experience of pain (10/77, 13%). HRQoL appeared to improve after surgery. Pain was a negative predictor of HRQoL. Conclusion: Current data on the determinants of HRQoL in DCM are limited, contradictory and heterogeneous. Limitations of this systematic review include lack of distinction between DCM subtypes and heterogenous findings amongst the papers in which HRQoL is measured postoperatively or post-diagnosis. This highlights the need for greater standardisation in DCM research to allow further synthesis. Studies of greater precision are necessary to account for HRQoL being complex, multi-factorial and both time and context dependent.